2020
DOI: 10.36082/qjk.v14i2.108
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Self Efficacy Mengahadapi Bullying Di Sekolah

Abstract: Introduction: Bullying behavior becomes an unsettling problem at school. bullying cases have a major impact on the psychology of victims of bullying. Improper coping relationships can form negative behaviors. This study aims to improve Self-efficacy which plays an important role in overcoming bullying events. Method: this study uses a literature review method by searching the electronic data base PROQUEST, EBSCO, DOAJ, GOOGLE SCHOLAR, GATE RESEARCH with keywords: self-efficacy, bullying, victim intimidation. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
2
0
4
Order By: Relevance
“…The results of this study are in line with research conducted by 13 which shows there is a significant relationship between bullying behavior and self-efficacy in nursing students. In addition, the results of a qualitative study by 6 show that incidents of bullying have various impacts on the mental health or psychology of victims of bullying. Overcoming this impact, it is hoped that the support of teachers, parents, and closest friends can support in increasing the self-efficacy of victims of bullying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in line with research conducted by 13 which shows there is a significant relationship between bullying behavior and self-efficacy in nursing students. In addition, the results of a qualitative study by 6 show that incidents of bullying have various impacts on the mental health or psychology of victims of bullying. Overcoming this impact, it is hoped that the support of teachers, parents, and closest friends can support in increasing the self-efficacy of victims of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Research that states self-efficacy with the incidence of bullying obtained from the results of research by 5 said that high self-efficacy indicates that there is a higher probability of falling into a group, and the negative impact of bullying at school is relatively small. 6 found that self-efficacy affects how adolescents interpret environmental conditions, expectations, strategies, and actions taken to minimize the impact of bullying. Bullying has various effects on the mental health or psychology of victims of bullying.…”
Section: Introductionmentioning
confidence: 99%
“…Keperawatan merupakan profesi dimana perawat berfokus pada pemenuhan pelayanan dalam kebutuhan kesehatan yang berlandaskan pada ilmu keperawatan yang terdiri dari bio-psiko-sosio-spiritual (Situmorang, 2016). Ketua tim adalah perawat profesional yang diharapkan bisa menjadi sekelompok tenaga keperawatan dalam memberikan asuhan keperawatan kepada pasien baik dalam bentuk kooperatif maupun dalam bentuk kolaboratif (Arwani, 2010).…”
Section: Pendahuluanunclassified
“…Menurut Yusuf & Fahrudin (2012), perilaku bully merupakan satu dari banyak masalah tingkah laku dan disiplin di kalangan murid sekolah dewasa ini, perilaku bully secara langsung atau tidak langsung merupakan sebagian dari tingkah laku agresif. Kemudian menurut Anggraini, et al, (2020) mengungkapkan bahwa korban bullying yang mempunyai self-efficacy dalam mengatasi dampak negatif perilaku bullying mampu menggunakan strategi dan mendesain serangkaian kegiatan untuk merubah keadaan. Hal ini diperkuat oleh Amawidyati & Muhammad (2017), mengungkapkan bahwa tentang program psikoedukasi bullying efektif untuk meningkatkan efikasi diri setiap individu.…”
Section: Pendahuluanunclassified
“…Hasil ini didukung oleh temuan yang menunjukkan bahwa responden yang menerima perlakuan bullying rendah dan efikasi diri tinggi sebanyak 55 (27,5%) responden, serta responden yang menerima perlakuan bullying tinggi dan efikasi rendah sebanyak 73 (36,5%) responden. Hal ini diperkuat oleh penelitian dari Anggraini, Azizah Heru et al, (2020) ketika seorang remaja mengalami perilaku bullying akan mendapatkan dampak negatif dimana remaja tersebut akan mengalami gangguan psikologi, tertekan, merasa rendah diri dan tidak berharga serta hilangnya atau rendahnya kepercayaan terhadap diri sendiri dalam menangani masalah atau persoalan yang sedang dialaminya hal ini yang membuat sehingga efikasi dari remaja dapat menurun.…”
Section: Diskusiunclassified